Crashworthiness analysis of new curved Kirigami corrugated structures - Ruofei Yan; Zhejian Li; Hong Hao; Wensu Chen (Materials & Design)
In this study, conventional corrugated (CC) units with curve-edged cross-section profiles including semi-period sinusoidal, one-period sinusoidal, elliptical, and arc shapes, were modified to form the respective new Kirigami corrugated (KC) units to improve their performances for applications in various fields. Both CC and KC specimens were first prepared and quasi-static compressed to examine their crashworthiness and were used for calibrating the numerical model. Parametric studies were conducted where aspect ratio and unit length were applied as key parameters. Dynamic crushing at velocities of 10 m/s and 25 m/s were also simulated. Significant enhancements in energy absorption capacities were observed in curved KC structures compared with their respective conventional forms. The KC configurations with aspect ratios ranging from 0.4 to 0.6 exhibit superior performance, with shorter units resulting in higher specific energy absorption but larger force fluctuations. Furthermore, the curved KC units demonstrated an upward trend of force–displacement curves and lower initial peak force indicating great potential in energy absorption applications.